2007
DOI: 10.1146/annurev.pathol.2.010506.092038
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Based Therapy for Myocardial Ischemia and Infarction: Pathophysiological Mechanisms

Abstract: Cell-based cardiac repair has emerged as an attractive approach to preventing or reversing heart failure resulting from myocyte dysfunction-e.g., due to infarction-and to enhancing the development of collaterals in patients with symptoms of myocardial ischemia. These two problems involve both overlapping and differing mechanisms, and these differences must be considered in cell-based therapies. In terms of myocardial dysfunction due to infarction, only committed cardiomyocytes have been shown to form new myoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
157
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(161 citation statements)
references
References 154 publications
1
157
0
Order By: Relevance
“…Many strategies being pursued to restore heart function involve repopulating the heart with exogenously delivered cells, either by direct injection [1,2] or intravascular delivery. The first attempts to repopulate the scarred aftermath of myocardial infarction (MI) were performed over fifteen years ago [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many strategies being pursued to restore heart function involve repopulating the heart with exogenously delivered cells, either by direct injection [1,2] or intravascular delivery. The first attempts to repopulate the scarred aftermath of myocardial infarction (MI) were performed over fifteen years ago [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The first attempts to repopulate the scarred aftermath of myocardial infarction (MI) were performed over fifteen years ago [3][4][5]. Since that time, interest in cell transplantation for the prevention and treatment of heart failure has exploded, leading to multiple animal studies and clinical trials [2]. These studies showed that a panoply of cells injected into the myocardium both can change the nature of the scar and improve post-infarction cardiac function.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several approaches to increase the number of CMs within injured myocardium have been attempted, including (1) activation and stimulation of host myocardial regeneration by transplanted cells via angiogenic and=or paracrine effects, 4,5 (2) direct transplantation of functional CMs or myogenic cells, [6][7][8] and (3) implantation of tissue constructs containing CMs. 9,10 In the latter two cases, the ideal donor CMs possess a high potential for division during cell preparation and potential for further proliferation following implantation to form a viable myocardial tissue within the surrounding injured recipient myocardium.…”
Section: Introductionmentioning
confidence: 99%
“…relative abundance | lipid-mediated | TIPeR | microarray | patch clamp C ardiomyocytes are among the most sought-after cells in regenerative medicine because they may help to repair an injured heart by replacing lost tissue (1,2). Functional cardiomyocyte-like cells have been induced from embryonic stem cells (ESCs), induced from pluripotent stem cells (iPSCs), and generated from direct conversion of fibroblasts using defined transcription factor transduction (3)(4)(5)(6)(7).…”
mentioning
confidence: 99%